Tratamento de efluentes de laboratórios contendo formaldeído utilizando peróxido de hidrogênio, ozônio e peróxido de hidrogênio + ozônio - Silva, Michele Goulart da (Universidade do Vale do Rio dos Sinos, 2015)
The aqueous solution of formaldehyde, known as formaldehyde, is used by various sectors of industry. In hospitals, laboratories and universities, this substance has wide application in the preservation and fixation of tissues and parts of anatomy samples in concentrations ranging between 8 and 10%. In these activities, changes may occur in these solutions as evaporation of the solvent, dilution and clouding by changing some properties, may need to be replaced and / or replace the solutions for concentration adjustment. These practices lead to generation of wastewater, where in many cases the disposal is done by transferring the pollutant so that contractors do the treatment and / or proper disposal on the environment. The lack of specific legislation is one of the factors that difficult the process of treatment of this effluent. furthermore, formaldehyde, although isn’t a generated waste during large-scale, considering its mass, is a highly impacting effluent to the environment because of their toxicity and persistence. In this work, the effluent containing formaldehyde generated by UNISINOS laboratories was characterized as its concentration, pH, COD, BOD, total suspended solids, volatile suspended solids, apparent color, true color and turbidity. A preliminary evaluation with synthetic wastewater was performed which demonstrated that: 1) the hight pH favors the oxidation reaction with H2O2, 2) as higher the concentration of the pollutant the oxidant performance is lower, 3) the use of buffer solution improves significantly the reduction of formaldehyde and 4) the use of ozone in medium pH haven’t promoted the degradation of the effluent. With the raw wastewater, the buffer solution haven't had the same performance when oxidized with H2O2. Thus, have been evaluated the oxidants as H2O2, O3 and H2O2 combined with O3, in the degradation of effluents contaminated by formaldehyde with an initial concentration range of 2000 - 2500 mg/L. The assays have been monitored from the formaldehyde concentration, pH and COD. Using a formaldehyde / H2O2 ration by 1: 0.8 (w / w) and an ozone generator capacity of 9.2 to 10.3 g/hr after 72 hours of combined treatment of these two oxidizers, this method has able to remove between 70 and 95% formaldehyde, representing an average of 82% pollutant degradation. Evaluating the new emission standards, after treatment with the best performance as the reduction of formaldehyde concentration, the effluent didn’t meet the CONAMA Resolution 430/2011 that provides about the issuance of effluent into receiving bodies of water, but it brings the concentration of formaldehyde to a value close to 400 mg/L.
Keywords: Formaldeído; Tratamento de efluentes de laboratórios; Processos oxidativos; Descarte de resíduos perigosos; Formaldehyde; Laboratories wastewater treatment; Oxidation processes; Disposal of hazardous waste; ACCNPQ::Engenharias::Engenharia Civil